Photovoltaic panel synergistic coating based on nano conductive polymer and preparation method thereof

By applying nanoconductive polymer enhancing coating on photovoltaic panels, the problem of insufficient anti-aging performance and photoelectric conversion efficiency of photovoltaic module enhancing layers is solved, and higher conductivity, light absorption range and durability are achieved, which improves the Overall performance of photovoltaic panels.

CN119432188AInactive Publication Date: 2025-02-14SHEYANG RES INST OF NANJING UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411797804.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The anti-aging performance and photoelectric conversion efficiency of the existing photovoltaic module enhancing layers need to be improved.

Method used

Using a photovoltaic panel synergistic coating preparation method based on nanoconductive polymers, the nanotitanium dioxide is uniformly dispersed in the sodium polystyrene sulfonate molecule and combined with modified antioxidants and modified polysiloxane to form high A synergistic coating with crosslinking and good adhesion.

Benefits of technology

It improves the conductive properties and light absorption range of the enhancing coating, enhances the durability of ultraviolet light, extends the service life of the photovoltaic panel, and improves the photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005177235970000031
    Figure BDA0005177235970000031
  • Figure BDA0005177235970000032
    Figure BDA0005177235970000032
  • Figure BDA0005177235970000034
    Figure BDA0005177235970000034
Patent Text Reader

Abstract

The invention discloses a photovoltaic panel synergistic coating based on a nano conductive polymer and a preparation method thereof, belongs to the technical field of photovoltaic component coating synergism, and is used for solving the technical problem that the anti-aging performance of a photovoltaic component synergistic layer and the photoelectric conversion efficiency of a photovoltaic component need to be further improved in the prior art. The preparation method comprises the following steps: adding sodium p-styrenesulfonate, a modified antioxidant and N-methyl pyrrolidone into a reaction kettle under the protection of nitrogen, stirring until the system is dissolved and clarified, and adding modified titanium dioxide into the reaction kettle; according to the invention, polycondensates of modified titanium dioxide, a modified antioxidant, modified polysiloxane and sodium p-styrenesulfonate are enhanced by isocyanate propyl triethoxy silane, so that not only are the conductivity and light absorption performance of the synergistic coating effectively improved, but also the aging resistance and adhesion performance of the synergistic coating are improved; and the photovoltaic panel can maintain high photoelectric conversion efficiency in the long-term use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic component coating efficiency enhancement, and in particular to a photovoltaic panel efficiency enhancement coating based on nano conductive polymer and a preparation method thereof. Background Art

[0002] With the continuous growth of global energy demand and the enhancement of environmental protection awareness, solar energy, as a clean and renewable energy source, is receiving more and more attention and utilization. As the main equipment for solar power generation, the performance improvement and cost reduction of photovoltaic panels have always been the focus of research and development. Nano-conductive polymers, with their special structure and properties, show great application potential in photoelectrochemical solar cells. These polymers not only have good conductivity, but also have high stability and processability, which are very suitable for efficiency modification of photovoltaic panels.

[0003] Prior art, a Chinese invention patent with publication number CN116640507A, discloses a hydrophilic self-cleaning synergistic coating composition, coating and preparation method and application thereof, wherein the total weight of the hydrophilic self-cleaning synergistic coating composition is 100%, and it comprises 5-35wt% of modified silane hydrolyzate, 10-50wt% of nano-SiO2 particle dispersion, 0-5wt% of surfactant and 10-85wt% of a first solvent; wherein, the total weight of the raw materials used to prepare the modified silane hydrolyzate is 100%, and the raw materials comprise 1-30wt% of a silicon source, 0.1-5wt% of an alkaline catalyst, 0.1-3wt% of a modifier and 62.0-98.8wt% of a second solvent; the hydrophilic self-cleaning synergistic coating is a synergistic coating that integrates multiple functions of anti-reflection, dust resistance and self-cleaning. When applied to the surface of photovoltaic glass, it can improve the light transmittance of the glass to a certain extent, and can keep the surface of the photovoltaic panel used outdoors clean for a long time.

[0004] However, traditional photovoltaic modules are often exposed to direct ultraviolet light in actual applications. If the anti-ultraviolet performance of the enhancement layer is poor, the enhancement coating will easily turn yellow during use, reducing the transmittance of light. In addition, simply increasing the transmittance of the coating, due to mirror reflection, the photovoltaic module's absorption range of light is often limited, resulting in the need to further improve the photoelectric conversion efficiency of the photovoltaic module.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a photovoltaic panel enhancement coating based on nano-conductive polymer and a preparation method thereof, so as to solve the technical problem in the prior art that the anti-aging performance of the photovoltaic module enhancement layer and the photoelectric conversion efficiency of the photovoltaic module need to be further improved.

[0007] The purpose of the present invention can be achieved by the following technical solution: A method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymers comprises the following steps:

[0008] S1. Add sodium p-styrene sulfonate, modified antioxidant and N-methylpyrrolidone to a nitrogen-protected reactor and stir until the system is dissolved. Add modified titanium dioxide and modified polysiloxane to the reactor. Raise the temperature of the reactor to 85-95°C. Add initiator solution dropwise to the reactor. Keep the temperature for 6-8h. Add isocyanatepropyltriethoxysilane to the reactor. Stir for 30-50min. Post-treat to obtain a coating liquid precursor.

[0009] The synthetic reaction formula of the coating liquid precursor includes:

[0010] Reaction 1:

[0011]

[0012] Where:

[0013]

[0014] It is modified titanium dioxide.

[0015] Reaction 2

[0016]

[0017] The synthetic reaction mechanism of the coating liquid precursor is:

[0018] Modified titanium dioxide and modified polysiloxane are used as crosslinking agents. Under the action of an initiator, free radical addition reaction occurs on unsaturated double bonds on sodium styrene sulfonate, modified antioxidant, modified titanium dioxide and modified polysiloxane molecules to form a composite sodium polystyrene sulfonate modified with modified antioxidant, modified titanium dioxide and modified polysiloxane. Then, the isocyanate group on isocyanatepropyltriethoxysilane undergoes condensation reaction with active groups such as hydroxyl and amino groups on the molecular chain of the composite sodium polystyrene sulfonate, and triethoxysilane is introduced into the molecular chain of the composite sodium polystyrene sulfonate to prepare a coating liquid precursor.

[0019] S2, mixing the coating liquid precursor and the activation liquid evenly to obtain a coating liquid;

[0020] S3. Clean the surface of the photovoltaic panel to remove oil and dust, apply the coating liquid on the clean surface of the photovoltaic panel, transfer the photovoltaic panel to a drying oven at a temperature of 80-85°C, dry for 3-5 hours, and naturally cool to room temperature to form a 0.2±0.05mm thick synergistic coating on the photovoltaic panel.

[0021] Furthermore, in step S1, the amount ratio of sodium p-styrene sulfonate, modified antioxidant, N-methylpyrrolidone, modified titanium dioxide, modified polysiloxane, initiator solution and isocyanatepropyltriethoxysilane is 13g:2g:70mL:3g:4g:6g:2g, the initiator solution is composed of azobisisobutyronitrile and N-methylpyrrolidone in a weight ratio of 1:5, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 95-105°C, and part of the solvent is evaporated under reduced pressure to obtain a coating liquid precursor with a viscosity of 70-90Pa·s; in step S2, the weight ratio of the coating liquid precursor to the activation liquid is 40:2-3, and the activation liquid is 0.1-0.5mol / L ammonia water.

[0022] Furthermore, the preparation method of the modified antioxidant is as follows: adding isophorone diisocyanate and ethyl acetate into a nitrogen-protected reactor and stirring, raising the temperature of the reactor to 40-50°C, dropping allyl acetic acid into the reactor, and keeping the temperature for 60-80 minutes, dropping antioxidant 1010 solution into the reactor, raising the temperature of the reactor to 65-75°C, keeping the temperature for 2.5-3.5 hours, and post-treating to obtain the modified antioxidant.

[0023] The synthetic reaction formula of the modified antioxidant is:

[0024]

[0025] Where:

[0026]

[0027] The synthetic reaction mechanism of the modified antioxidant is:

[0028] In an inert gas protection environment, an isocyanate group on the isophorone diisocyanate molecule undergoes a condensation reaction with a carboxyl group on the allyl acetic acid molecule to form an isocyanate-terminated intermediate on the allyl acetic acid molecule, and then the isocyanate group on the intermediate reacts with a hydroxyl group on the antioxidant 1010 molecule to form an olefin double bond modification on the antioxidant 1010 molecule, thereby preparing a modified antioxidant.

[0029] Furthermore, the dosage ratio of isophorone diisocyanate, allyl acetic acid and antioxidant 1010 is 1 mol:1 mol:1 mol, the dosage ratio of isophorone diisocyanate and ethyl acetate is 1 g:7 mL, the antioxidant 1010 solution consists of antioxidant 1010 and ethyl acetate in a weight ratio of 1:3, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is kept at 65-75° C., and the solvent is evaporated under reduced pressure to obtain a modified antioxidant.

[0030] Further, the modified titanium dioxide is processed by the following steps:

[0031] A1. Tetrabutyl titanate and n-hexanoic acid are added to a reactor and stirred for 5-10 minutes. Deionized water is added to the reactor and stirred for 20-30 minutes. The reactor is sealed, the temperature of the heat exchange medium is increased to 220-240°C, and the heat treatment is carried out for 3-5 hours. Nano titanium dioxide is obtained by post-treatment;

[0032] A2. Add nano titanium dioxide, anhydrous ethanol and KH-570 into a reactor and stir. The temperature of the reactor is raised to 50-60° C., and the catalyst solution is added into the reactor. The reaction mixture is stirred for 60-80 min at a temperature-insulated temperature. The modified titanium dioxide is obtained by post-treatment.

[0033] The synthetic reaction mechanism of modified titanium dioxide is:

[0034] n-Hexanoic acid is used as a solvent or co-solvent to help tetrabutyl titanate to be better dispersed in the system. The addition of deionized water promotes the hydrolysis and disconnection of ester bonds in tetrabutyl titanate to form hydroxyl compounds. The hydroxyl compounds generated by hydrolysis further undergo condensation reactions to form larger aggregates or colloidal particles. In addition, n-hexanoic acid can undergo an ester exchange reaction with tetrabutyl titanate to generate titanate containing n-hexanoate ions, forming long-chain alkane modifications on the outside of the colloidal particles and preventing agglomeration between particles through a steric hindrance effect, thereby stabilizing the particles, making the reaction more sufficient and uniform, and ensuring its stabilizing effect on the colloidal particles to prepare nano-titanium dioxide; in an alkaline environment, the siloxane bonds on the KH-570 molecules are disconnected to form silanol modifications on the surface of the nano-titanium dioxide, forming a surface coating modification of polysiloxane containing olefin double bonds, and preparing modified titanium dioxide.

[0035] Furthermore, in step A1, the amount ratio of tetrabutyl titanate, hexanoic acid and deionized water is 13g:2g:15mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed with anhydrous ethanol for 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain nano titanium dioxide; in step A2, the amount ratio of the nano titanium dioxide, anhydrous ethanol, KH-570 and catalyst solution is 10g:100mL:3g:10mL, the catalyst solution is 0.3-0.5mol / L sodium hydroxide solution, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration is performed, the filter cake is washed with purified water until neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain modified titanium dioxide.

[0036] Furthermore, the preparation method of modified polysiloxane is: octamethyl silicone oil, aminopropylmethyldiethoxysilane, tetramethyldivinyldisiloxane and a catalyst are added to a reaction kettle and stirred, the temperature of the reaction kettle is increased to 80-90° C., the reaction is kept warm for 5-7 hours, and the modified polysiloxane is obtained by post-treatment.

[0037] The synthetic reaction formula of modified polysiloxane is:

[0038]

[0039] The synthetic reaction mechanism of modified polysiloxane is:

[0040] Under the catalytic action of sulfuric acid, the ethoxy groups in aminopropylmethyldiethoxysilane and tetramethyldivinyldisiloxane are hydrolyzed to generate corresponding silanols, which then undergo condensation reactions with the siloxy segments of octamethylsilicone oil to form olefin-terminated polysiloxanes and introduce functional silanes into the polysiloxane network to prepare modified polysiloxanes.

[0041] Furthermore, the amount ratio of octamethyl silicone oil, aminopropylmethyldiethoxysilane, tetramethyldivinyldisiloxane and catalyst is 25g:3g:1g:4g, the catalyst is 25-35wt% sulfuric acid, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, purified water and toluene are added to the reactor, stirred for 30-40 minutes, allowed to stand for liquid separation, the organic phase is washed with purified water to neutrality, the organic phase is transferred to the reactor, the temperature of the reactor is increased to 90-100°C, and reduced pressure distillation is performed until no liquid is produced to obtain modified polysiloxane.

[0042] Among them, the photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer is obtained by processing using the preparation method of the photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer.

[0043] The present invention has the following beneficial effects:

[0044] 1. The photovoltaic panel synergistic coating based on nano-conductive polymer provided by the present invention is prepared by combining a coating liquid precursor and an activating liquid, promoting the hydrolysis of siloxane bonds in the coating liquid precursor molecules, and curing at high temperature. While increasing the degree of cross-linking between the synergistic coating molecules, the adhesion level between the synergistic coating and the photovoltaic panel surface is improved. When preparing the coating liquid precursor, nano-titanium dioxide is uniformly dispersed in sodium polystyrene sulfonate molecules to improve the light absorption range and conductivity of the synergistic coating, thereby improving the photoelectric conversion efficiency of the photovoltaic module. In addition, titanium dioxide ions and antioxidants act together on the synergistic coating to avoid yellowing and discoloration of the synergistic coating during use, thereby improving the UV aging resistance of the synergistic coating.

[0045] 2. The photovoltaic panel synergistic coating based on nano-conductive polymer provided by the present invention optimizes the preparation method of titanium dioxide particles and performs surface modification on them, which not only effectively improves the dispersibility and surface activity of modified titanium dioxide in organic matter, but also enables the modified titanium dioxide to be evenly dispersed in organic solutions. The olefin double bonds on the modified titanium dioxide are used as active sites to increase the degree of crosslinking between sodium polystyrene sulfonate molecules, forming a tighter network structure, and improving the conductivity of the coating. At the same time, it is beneficial to reduce the pores and defects in the coating, improve the density and uniformity of the coating, and have better conductivity, which is beneficial to the collection and transmission of charges in the photovoltaic panel. Moreover, the introduction of modified titanium dioxide can increase the light scattering center of the coating, so that the incident light is scattered multiple times inside the coating, and the propagation path of the light in the coating is extended. In addition, due to the increase in the degree of crosslinking and the increase in the light scattering center, the light absorption efficiency of the coating may be improved, so that more light can be absorbed by the coating and converted into other forms of energy, thereby improving the photoelectric conversion efficiency of the photovoltaic panel.

[0046] 3. The photovoltaic panel synergistic coating based on nano-conductive polymer provided by the present invention introduces polysiloxane segments and antioxidant 1010 into the sodium polystyrene sulfonate molecules of the coating liquid precursor. The polysiloxane segments have excellent flexibility and outstanding weather resistance, and the bond energy of the Si-O bonds is relatively high and the bond angle is relatively large, so that the molecular chain is easy to rotate and bend. The olefin end groups on the modified polysiloxane molecular segments can increase the degree of cross-linking between molecules, and at the same time, the modified polysiloxane is added to the sodium polystyrene sulfonate molecular chain in the form of cross-linking and intercalation, thereby improving the flexibility of the sodium polystyrene sulfonate molecular chain, thereby reducing the risk of molecular chain breakage under ultraviolet light irradiation. Antioxidant 1010 can not only resist ultraviolet light irradiation, but also has excellent thermal stability. It cooperates with nano-titanium dioxide particles to prevent the synergistic coating from being degraded due to thermal oxidation, so that the photovoltaic panel can maintain a high photoelectric conversion efficiency during long-term use, and reduce the performance degradation caused by coating aging, shedding, etc. DETAILED DESCRIPTION

[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Example 1

[0049] This embodiment provides a method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer, comprising the following steps:

[0050] S1. Preparation of modified antioxidant

[0051] Weigh: 117.8 g of antioxidant 1010 and 353.4 g of ethyl acetate, add into a beaker and stir until the system is dissolved to obtain an antioxidant 1010 solution for later use;

[0052] Weigh: 22.2 g of isophorone diisocyanate and 155.4 mL of ethyl acetate are added to a nitrogen-protected reactor with stirring, the temperature of the reactor is raised to 40°C, 10.0 g of allyl acetic acid is added dropwise to the reactor, and the reaction is kept warm for 60 minutes. Antioxidant 1010 solution is added dropwise to the reactor, the temperature of the reactor is raised to 65°C, and the reaction is kept warm for 2.5 hours. The temperature of the reactor is kept at 65°C, and the solvent is evaporated under reduced pressure to obtain a modified antioxidant.

[0053] S2. Preparation of modified titanium dioxide

[0054] Weigh: 52g of tetrabutyl titanate and 8g of n-hexanoic acid are added to the reactor and stirred for 5min, 60mL of deionized water is added to the reactor, and the mixture is stirred for 20min. The reactor is sealed, the temperature of the heat exchange medium is increased to 220°C, and the mixture is kept warm for 3h. The temperature of the reactor is lowered to room temperature, and the filter cake is filtered, and the filter cake is washed with anhydrous ethanol for 3 times and then dried. The filter cake is transferred to a drying oven at 60°C and vacuum dried to constant weight to obtain nano titanium dioxide;

[0055] Weigh: 50 g of nano titanium dioxide, 500 mL of anhydrous ethanol and 15 g of KH-570, add them into a reactor and stir, raise the temperature of the reactor to 50°C, add 50 mL of 0.3 mol / L sodium hydroxide solution into the reactor, keep warm and stir for 60 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain modified titanium dioxide.

[0056] S3. Preparation of modified polysiloxane

[0057] Weigh: 100 g of octamethyl silicone oil, 12 g of aminopropylmethyldiethoxysilane, 4 g of tetramethyldivinyldisiloxane and 16 g of 25 wt% sulfuric acid, add them to a reactor and stir, raise the temperature of the reactor to 80°C, keep the reaction warm for 5 hours, lower the temperature of the reactor to room temperature, add 500 mL of purified water and 500 mL of toluene to the reactor, stir for 30 minutes, let stand and separate the liquids, wash the organic phase with purified water until neutral, transfer the organic phase to the reactor, raise the temperature of the reactor to 90°C, and distill under reduced pressure until no liquid is produced to obtain modified polysiloxane.

[0058] S4. Preparation of coating liquid

[0059] Weigh: 130 g of sodium p-styrene sulfonate, 20 g of modified antioxidant and 700 mL of N-methylpyrrolidone, add them into a nitrogen-protected reactor and stir until the system is dissolved, add 30 g of modified titanium dioxide and 40 g of modified polysiloxane into the reactor to obtain a mixed solution;

[0060] Azobisisobutyronitrile and N-methylpyrrolidone are uniformly mixed in a weight ratio of 1:5 to obtain an initiator solution;

[0061] The temperature of the reactor was raised to 85°C, 60 g of the initiator solution was added dropwise to the reactor, and the mixture was kept warm for 6 h. 20 g of isocyanatepropyltriethoxysilane was added to the reactor, and the mixture was stirred for 30 min. The temperature of the reactor was raised to 95°C, and part of the solvent was evaporated under reduced pressure to obtain a coating liquid precursor with a viscosity of 70 Pa·s.

[0062] The coating liquid precursor and 0.1 mol / L ammonia water were uniformly mixed in a weight ratio of 40:2 to obtain a coating liquid.

[0063] S5. Preparation of synergistic coating

[0064] Use 2 mol / L sodium hydroxide solution and acetone to clean the surface of the solar photovoltaic panel to remove oil and dust on the surface;

[0065] Use a spin coater to spin at a speed of 1000 rpm for 10 seconds to evenly spin coat the coating liquid on the clean surface of the photovoltaic panel to form a uniform coating layer;

[0066] The solar photovoltaic panel with a uniform coating layer was transferred to a drying oven at a temperature of 80°C, dried for 3 hours, and naturally cooled to room temperature to form a 0.15 mm thick synergistic coating on the photovoltaic panel.

[0067] Example 2

[0068] This embodiment provides a method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer, comprising the following steps:

[0069] S1. Preparation of modified antioxidant

[0070] Weigh: 117.8 g of antioxidant 1010 and 353.4 g of ethyl acetate, add into a beaker and stir until the system is dissolved to obtain an antioxidant 1010 solution for later use;

[0071] Weigh: 22.2 g of isophorone diisocyanate and 155.4 mL of ethyl acetate are added to a nitrogen-protected reactor with stirring, the temperature of the reactor is raised to 45°C, 10.0 g of allyl acetic acid is added dropwise to the reactor, and the reaction is kept warm for 70 minutes. Antioxidant 1010 solution is added dropwise to the reactor, the temperature of the reactor is raised to 70°C, and the reaction is kept warm for 3.0 hours. The temperature of the reactor is kept at 70°C, and the solvent is evaporated under reduced pressure to obtain a modified antioxidant.

[0072] S2. Preparation of modified titanium dioxide

[0073] Weigh: 52g of tetrabutyl titanate and 8g of n-hexanoic acid, add them into the reactor and stir for 7min, add 60mL of deionized water into the reactor, keep warm and stir for 25min, seal the reactor, increase the temperature of the heat exchange medium to 230°C, keep warm for 4h, lower the temperature of the reactor to room temperature, filter, wash the filter cake with anhydrous ethanol 3 times and then drain, transfer the filter cake to a drying oven at 65°C, and vacuum dry to constant weight to obtain nano titanium dioxide;

[0074] Weigh: 50 g of nano titanium dioxide, 500 mL of anhydrous ethanol and 15 g of KH-570, add them into a reactor and stir, raise the temperature of the reactor to 55°C, add 50 mL of 0.4 mol / L sodium hydroxide solution into the reactor, keep warm and stir for 70 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry it to constant weight to obtain modified titanium dioxide.

[0075] S3. Preparation of modified polysiloxane

[0076] Weigh: 100 g of octamethyl silicone oil, 12 g of aminopropylmethyldiethoxysilane, 4 g of tetramethyldivinyldisiloxane and 16 g of 30 wt% sulfuric acid, add to the reactor and stir, raise the temperature of the reactor to 85 ° C, keep warm for 6 hours, lower the temperature of the reactor to room temperature, add 500 mL of purified water and 500 mL of toluene to the reactor, stir for 35 minutes, stand and separate the liquids, wash the organic phase with purified water until neutral, transfer the organic phase to the reactor, raise the temperature of the reactor to 95 ° C, and distill under reduced pressure until no liquid is produced to obtain modified polysiloxane.

[0077] S4. Preparation of coating liquid

[0078] Weigh: 130 g of sodium p-styrene sulfonate, 20 g of modified antioxidant and 700 mL of N-methylpyrrolidone, add them into a nitrogen-protected reactor and stir until the system is dissolved, add 30 g of modified titanium dioxide and 40 g of modified polysiloxane into the reactor to obtain a mixed solution;

[0079] Azobisisobutyronitrile and N-methylpyrrolidone are uniformly mixed in a weight ratio of 1:5 to obtain an initiator solution;

[0080] The temperature of the reactor was raised to 90°C, 60 g of the initiator solution was added dropwise to the reactor, and the mixture was kept warm for 7 h. 20 g of isocyanatepropyltriethoxysilane was added to the reactor, and the mixture was stirred for 40 min. The temperature of the reactor was raised to 100°C, and part of the solvent was evaporated under reduced pressure to obtain a coating liquid precursor with a viscosity of 80 Pa·s.

[0081] The coating liquid precursor and 0.3 mol / L ammonia water were uniformly mixed in a weight ratio of 40:2.5 to obtain a coating liquid.

[0082] S5. Preparation of synergistic coating

[0083] Use 2.5 mol / L sodium hydroxide solution and acetone to clean the surface of the solar photovoltaic panel to remove oil and dust on the surface;

[0084] Use a spin coater to spin at a speed of 2000 rpm for 20 seconds to evenly spin coat the coating liquid on the clean surface of the photovoltaic panel to form a uniform coating layer;

[0085] The solar photovoltaic panel with a uniform coating layer was transferred to a drying oven at a temperature of 83°C, dried for 4 hours, and naturally cooled to room temperature to form a 0.2 mm thick synergistic coating on the photovoltaic panel.

[0086] Example 3

[0087] This embodiment provides a method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer, comprising the following steps:

[0088] S1. Preparation of modified antioxidant

[0089] Weigh: 117.8 g of antioxidant 1010 and 353.4 g of ethyl acetate, add into a beaker and stir until the system is dissolved to obtain an antioxidant 1010 solution for later use;

[0090] Weigh: 22.2 g of isophorone diisocyanate and 155.4 mL of ethyl acetate are added to a nitrogen-protected reactor with stirring, the temperature of the reactor is raised to 50°C, 10.0 g of allyl acetic acid is added dropwise to the reactor, and the reaction is kept warm for 80 minutes. Antioxidant 1010 solution is added dropwise to the reactor, the temperature of the reactor is raised to 75°C, and the reaction is kept warm for 3.5 hours. The temperature of the reactor is kept at 75°C, and the solvent is evaporated under reduced pressure to obtain a modified antioxidant.

[0091] S2. Preparation of modified titanium dioxide

[0092] Weigh: 52g of tetrabutyl titanate and 8g of n-hexanoic acid, add them into a reactor and stir for 10min, add 60mL of deionized water into the reactor, keep warm and stir for 30min, seal the reactor, increase the temperature of the heat exchange medium to 240°C, keep warm for 5h, lower the temperature of the reactor to room temperature, filter, wash the filter cake with anhydrous ethanol 3 times and then drain, transfer the filter cake to a drying oven at 70°C, and vacuum dry to constant weight to obtain nano titanium dioxide;

[0093] Weigh: 50 g of nano titanium dioxide, 500 mL of anhydrous ethanol and 15 g of KH-570, add them into a reactor and stir, raise the temperature of the reactor to 60°C, add 50 mL of 0.5 mol / L sodium hydroxide solution into the reactor, keep warm and stir for 80 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 80°C, and vacuum dry it to constant weight to obtain modified titanium dioxide.

[0094] S3. Preparation of modified polysiloxane

[0095] Weigh: 100 g of octamethyl silicone oil, 12 g of aminopropylmethyldiethoxysilane, 4 g of tetramethyldivinyldisiloxane and 16 g of 35 wt% sulfuric acid, add to the reactor and stir, raise the temperature of the reactor to 90°C, keep warm for 7 hours, lower the temperature of the reactor to room temperature, add 500 mL of purified water and 500 mL of toluene to the reactor, stir for 40 minutes, let stand and separate the liquids, wash the organic phase with purified water until neutral, transfer the organic phase to the reactor, raise the temperature of the reactor to 100°C, and distill under reduced pressure until no liquid is produced to obtain modified polysiloxane.

[0096] S4. Preparation of coating liquid

[0097] Weigh: 130 g of sodium p-styrene sulfonate, 20 g of modified antioxidant and 700 mL of N-methylpyrrolidone, add them into a nitrogen-protected reactor and stir until the system is dissolved, add 30 g of modified titanium dioxide and 40 g of modified polysiloxane into the reactor to obtain a mixed solution;

[0098] Azobisisobutyronitrile and N-methylpyrrolidone are uniformly mixed in a weight ratio of 1:5 to obtain an initiator solution;

[0099] The temperature of the reactor was raised to 95°C, 60 g of the initiator solution was added dropwise to the reactor, and the mixture was kept warm for 8 h. 20 g of isocyanatepropyltriethoxysilane was added to the reactor, and the mixture was stirred for 50 min. The temperature of the reactor was raised to 105°C, and part of the solvent was evaporated under reduced pressure to obtain a coating liquid precursor with a viscosity of 90 Pa·s.

[0100] The coating liquid precursor and 0.5 mol / L ammonia water were uniformly mixed in a weight ratio of 40:3 to obtain a coating liquid.

[0101] S5. Preparation of synergistic coating

[0102] Use 3 mol / L sodium hydroxide solution and acetone to clean the surface of the solar photovoltaic panel to remove oil and dust on the surface;

[0103] Use a spin coater to spin at a speed of 3000 rpm for 30 seconds to evenly spin coat the coating liquid on the clean surface of the photovoltaic panel to form a uniform coating layer;

[0104] The solar photovoltaic panel with a uniform coating layer was transferred to a drying oven at a temperature of 85°C, dried for 5 hours, and naturally cooled to room temperature to form a 0.25 mm thick synergistic coating on the photovoltaic panel.

[0105] Comparative Example 1

[0106] The difference between this comparative example and Example 3 is that in step S2, commercially available nano titanium dioxide is used to replace the nano titanium dioxide used in the preparation process of modified titanium dioxide.

[0107] Comparative Example 2

[0108] The difference between this comparative example and Example 3 is that step S3 is omitted and modified polysiloxane is not added in step S4.

[0109] Comparative Example 3

[0110] The difference between this comparative example and Example 3 is that in step S4, no modified titanium dioxide is added.

[0111] Comparative Example 4

[0112] The difference between this comparative example and Example 3 is that in step S4, the coating liquid is replaced by a coating liquid precursor.

[0113] Performance Test:

[0114] The reflectance of the samples prepared in Examples 1-3 and Comparative Examples 1-4 was measured with reference to the standard JB / T 8226.1-1999 "Anti-reflection coating for optical parts";

[0115] The surface resistance values ​​of the samples prepared in Examples 1-3 and Comparative Examples 1-4 were measured with reference to the standard JB / T 5588-1991 "Conductive Film Coatings for Optical Parts";

[0116] The samples were exposed to light according to method A in standard GB / T 23987-2009 "Exposure of paint and varnish coatings to fluorescent ultraviolet light and water", and then the gloss loss levels of the samples prepared in Examples 1-3 and Comparative Examples 1-4 were evaluated according to standard GB / T 1766-2008 "Rating method for aging of paint and varnish coatings";

[0117] The adhesion grades of the samples prepared in Examples 1-3 and Comparative Examples 1-4 were measured with reference to the standard GB / T 9286-2021 "Scratch test for paints and varnishes";

[0118] Refer to the standard GB / T 34160-2017 "Test method for photoelectric conversion efficiency of ground photovoltaic modules" to measure the photoelectric conversion efficiency of photovoltaic modules, and then follow the formula: The change in the photoelectric conversion efficiency of the sample is calculated, where: η1 is the photoelectric conversion efficiency of the photovoltaic module after coating the synergistic coating, η0 is the photoelectric conversion efficiency of the photovoltaic module before coating the synergistic coating. The specific test results are shown in Table 1 below.

[0119] Table 1-Performance test data of samples

[0120]

[0121] Data Analysis:

[0122] Comparative analysis of the data in Table 1 above shows that after the photovoltaic module is coated with the synergistic coating prepared by the present invention, the reflectance of the material to visible light is reduced to 2.4%, the surface resistance is reduced to 68.2Ω / sq, the photoelectric conversion efficiency is increased by 19.5%, and it has good UV aging resistance and high adhesion performance. All performance parameters are better than those of the comparative example;

[0123] It is explained that the present invention is to block-modify sodium polystyrene sulfonate by modified titanium dioxide, modified antioxidant and modified polysiloxane, and then enhance the activation by isocyanatepropyltriethoxysilane and activation liquid, which not only effectively improves the conductivity and light absorption properties of the synergistic coating, but also improves its aging resistance and adhesion properties, so that the photovoltaic panel can maintain a high photoelectric conversion efficiency during long-term use.

[0124] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymers, characterized in that: The following steps are involved: S1. Add sodium p-styrene sulfonate, modified antioxidant, hexafluorobutyl methacrylate and N-methylpyrrolidone into a nitrogen-protected reactor and stir until the system is dissolved. Add modified titanium dioxide and modified polysiloxane into the reactor, increase the temperature of the reactor to 85-95° C., dropwise add initiator solution into the reactor, keep the temperature for reaction for 6-8 hours, add isocyanatepropyltriethoxysilane into the reactor, stir for 30-50 minutes, and perform post-treatment to obtain a coating liquid precursor. S2, mixing the coating liquid precursor and the activation liquid evenly to obtain a coating liquid; S3. Clean the surface of the photovoltaic panel to remove oil and dust, apply the coating liquid on the clean surface of the photovoltaic panel, transfer the photovoltaic panel to a drying oven at a temperature of 80-85°C, dry for 3-5 hours, and naturally cool to room temperature to form a 0.2±0.05mm thick synergistic coating on the photovoltaic panel.

2. The method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer according to claim 1, characterized in that: In step S1, the amount ratio of sodium p-styrene sulfonate, modified antioxidant, hexafluorobutyl methacrylate, N-methylpyrrolidone, modified titanium dioxide, modified polysiloxane, initiator solution and isocyanatepropyltriethoxysilane is 13g:2g:70mL:3g:4g:6g:2g, and the initiator solution is composed of azobisisobutyronitrile and N-methylpyrrolidone in a weight ratio of 1:5; in step S2, the weight ratio of the coating liquid precursor and the activation liquid is 40:2-3, and the activation liquid is 0.1-0.5mol / L ammonia water.

3. The method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer according to claim 1, characterized in that: The preparation method of the modified antioxidant is as follows: adding isophorone diisocyanate and ethyl acetate into a nitrogen-protected reactor and stirring, raising the temperature of the reactor to 40-50°C, dropping allyl acetic acid into the reactor, and keeping the temperature for reaction for 60-80 minutes, dropping an antioxidant 1010 solution into the reactor, raising the temperature of the reactor to 65-75°C, and keeping the temperature for reaction for 2.5-3.5 hours, and post-treating to obtain the modified antioxidant.

4. The method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer according to claim 3, characterized in that: The dosage ratio of isophorone diisocyanate, allyl acetic acid and antioxidant 1010 is 1 mol:1 mol:1 mol, the dosage ratio of isophorone diisocyanate and ethyl acetate is 1 g:7 mL, and the antioxidant 1010 solution consists of antioxidant 1010 and ethyl acetate in a weight ratio of 1:

3.

5. The method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer according to claim 1, characterized in that: Modified titanium dioxide is processed by the following steps: A1. Tetrabutyl titanate and n-hexanoic acid are added to a reactor and stirred for 5-10 minutes. Deionized water is added to the reactor and stirred for 20-30 minutes. The reactor is sealed, the temperature of the heat exchange medium is increased to 220-240°C, and the heat treatment is carried out for 3-5 hours. Nano titanium dioxide is obtained by post-treatment; A2. Add nano titanium dioxide, anhydrous ethanol and KH-570 into a reactor and stir. The temperature of the reactor is raised to 50-60° C., and the catalyst solution is added into the reactor. The reaction mixture is stirred for 60-80 min at a temperature-insulated temperature. The modified titanium dioxide is obtained by post-treatment.

6. The method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer according to claim 5, characterized in that: In step A1, the dosage ratio of tetrabutyl titanate, hexanoic acid and deionized water is 13g:2g:15mL; in step A2, the dosage ratio of nano-titanium dioxide, anhydrous ethanol, KH-570 and catalyst solution is 10g:100mL:3g:10mL, and the catalyst solution is 0.3-0.5mol / L sodium hydroxide solution.

7. The method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer according to claim 1, characterized in that: The preparation method of modified polysiloxane is as follows: octamethyl silicone oil, aminopropylmethyldiethoxysilane, tetramethyldivinyldisiloxane and a catalyst are added into a reaction kettle and stirred, the temperature of the reaction kettle is increased to 80-90° C., the reaction is kept warm for 5-7 hours, and the modified polysiloxane is obtained by post-treatment.

8. The method for preparing a photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer according to claim 7, characterized in that: The usage ratio of the octamethyl silicone oil, aminopropylmethyldiethoxysilane, tetramethyldivinyldisiloxane and the catalyst is 25g:3g:1g:4g, and the catalyst is 25-35wt% sulfuric acid.

9. Photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer, characterized in that: The photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer is obtained by processing using the preparation method of the photovoltaic panel efficiency-enhancing coating based on nano-conductive polymer as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Hydrophilic self-cleaning synergistic coating composition, coating as well as preparation method and application of hydrophilic self-cleaning synergistic coating composition

    CN116640507A